Languages, literature & cultures - Jowati Juhary (Penerbit Universiti Pertahanan Nasional Malaysia, 2013)
This volume comprises five articles that examine issues and challenges of English and foreign language learning and literature appreciation and, how all these are influenced by cultural values of the speakers.